Los significados otorgados a las relaciones adolescentes desde la comunidad escolar - Alvarez-Uria, Amaia (Revista electrónica interuniversitaria de formación del profesorado, 2017)
The use of social networks have increased situations of harassment and gender violence in adolescence. The aim of this study was to determine how these relationships are perceived from the perspective of the school community. A case study was conducted to know the situations experienced in social networks in schools of Vitoria-Gasteiz. 470 teacher questionnaires of 30 schools were collected, and 7 focus groups with families, teachers and students were conducted. The results show that relationships between adolescents are mediated by stereotypes; the persistence of sexism, control and aggressiveness. Among the proposals for the future, the students propose discussion forums to share emotional aspects. Teachers propose to build a critical spirit with students by analyzing the subliminal messages of the networks. And families propose to review attitudes and behaviors through workshops.Con el uso de las redes sociales han aumentado las situaciones de acoso y violencia de género en la adolescencia. El objetivo de este trabajo es conocer cómo se perciben estas relaciones desde la mirada de la comunidad escolar. Se realizó un estudio de caso para conocer las situaciones vividas en las redes sociales en los centros educativos de Vitoria-Gasteiz. Se recogieron 470 cuestionarios del profesorado de 30 centros escolares, y se realizaron 7 grupos de discusión, con familias, profesorado y estudiantes. Los resultados muestran que las relaciones adolescentes están mediatizadas por los estereotipos; la persistencia del sexismo, el control y la agresividad. El alumnado reclama programas educativos de formación sobre el uso de las redes sociales